2018
DOI: 10.1016/j.cca.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of collection tubes during quantitative targeted metabolomics studies in human blood samples

Abstract: Serum samples provide higher sensitivity for biomarker discovery studies. Due to the presence of spurious amount of sarcosine in vacutainer EDTA tubes, plasma EDTA is not suitable for studies requiring accurate quantification of sarcosine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…These methods may provide additional constrains and reasons for choosing one sample type and collection protocol over the other. As described for metabolomics [140][141][142] , a common suggestion is to process samples as quickly as possible (e.g. < 30 min) and store these soon as possible at −80°C.…”
Section: Resultsmentioning
confidence: 99%
“…These methods may provide additional constrains and reasons for choosing one sample type and collection protocol over the other. As described for metabolomics [140][141][142] , a common suggestion is to process samples as quickly as possible (e.g. < 30 min) and store these soon as possible at −80°C.…”
Section: Resultsmentioning
confidence: 99%
“…Serum Versus Plasma: Whether serum or plasma is better for blood metabolomic studies has been addressed by direct comparison of metabolomic profiles from the two blood fractions as well as by the sensitivity of each to various pre-analytical variables. Seven studies directly investigated differences in metabolomic findings from serum and plasma samples [9,10,11,12,13,14,15]. Comparing nuclear magnetic resonance (NMR)-derived metabolomic profiles from four independent samples, Teahan et al [9] found that differences between serum and plasma were minimal.…”
Section: Resultsmentioning
confidence: 99%
“…Serum samples were prepared according to the manufacturer's instructions adding several stable isotope-labelled standards to the samples prior to the derivatization and extraction steps. Using LC/MS, up to 184 metabolites from 5 different compound classes, namely, acylcarnitines, amino acids, biogenic amines, glycerophospholipids, and sphingolipids can be quantified [20]. Sample order was randomized, and pooled quality control (QC) samples (minimum 3) were plated at different positions on the 96-well plate and injected multiple times for covariance variation (CV) calculation for data quality control.…”
Section: Oral Glucose Tolerance Test (Ogtt)mentioning
confidence: 99%